Menstruation associated hypocalcemic symptoms and serum calcium in patients with idiopathic hypoparathyroidism - Saha, Soma; Goswami, Ravinder (BMC endocrine disorders, 2014)
Background Some of the patients with idiopathic hypoparathyroidism (IHP) report symptoms of hypocalcemia during menstruation. There is limited data on this observation. Methods Twenty six menstruating women with IHP and 26 healthy controls were questioned regarding symptoms suggestive of hypocalcemia during menstruation. Twelve patients and eight controls were asked to prospectively monitor symptoms suggestive of hypocalcemia and premenstrual syndrome (PMS) if any, over two consecutive menstrual cycles. Serum ionized calcium (SiCa ++ ), total and albumin adjusted calcium and intact paratharmone (iPTH) were measured at eight points covering menstrual, immediate post-menstrual, mid-cycle and premenstrual phase. Results Twelve of the 26 (46.2%) patients with IHP reported hypocalcemic symptoms during menstruation as compared to none of the controls. During prospective monitoring, there was no specific trend of hypocalcemic symptoms with respect to the phase of menstrual cycle. The mean SiCa ++ , serum total and albumin-adjusted calcium, iPTH and inorganic-phosphorus measured over two menstrual cycles were not significantly different in either of the two study groups. None of the subjects had PMS. Conclusion Women with IHP do not show any trend of hypocalcemic symptoms or fluctuations in serum calcium over different phases of menstrual cycles. Therefore, patients with hypoparathyroidism linking hypocalcemic symptoms with menstruation should be reassured regarding lack of this association.